L’invention d’une tradition : le cas des Églises cowboys au Texas - Véronique Pioch-Eberhart (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
In this article, we address the question of the invention of traditions through the concrete example of the Cowboy Churches, recently added in the Christian landscape of the American West. Cowboy churches emerge from various traditional denominations. They do, however, offer a number of common features which, in our opinion, generate the invention of tradition.